Social Class Segregation in American Society As Portrayed in Edward Albee’s The Zoo Story - Lamria Butar-butar; Yohanes Tuaderu (LINGUA LITERA : journal of english linguistics and literature, 2017)
This paper discusses about social class segregation in American Society especially in Manhattan as portrayed in The Zoo Story written by Edward Albee in 1958. The segregation can be seen through the social intercourse between Peter and Jerry, the main characters in this play. These characters are positioned in different social class because of the difference of educational and economic background. The writers use various sources to enrich their perspective and analysis taken from books and online sources. This research stands on the sociological side to view the problem why segregation may occur in real social life. To develop a good elaboration on the data found in the drama, the writers use sociological theory proposed by Pierre Bourdieu that focuses on educational and economic capital as the main factors to segregate people in human society. After conducting the research, the writers found that there is a social class segregation in American Society which is depicted in The Zoo Story. This fact encourages most Americans to realize the what-so-called American Dream which aims to have a good and happy life based on freedom and equality in all aspects of life without considering the race, ethnicity, socioeconomic status, gender, religion, employment status, and so on.